Evaluation of the safety and therapeutic efficacy of multipotent adult progenitor cells in the treatment of canine bronchitis (Research, Society and Development, 2024)
Canine chronic bronchitis is a disease that is characterized by chronic inflammation of the airways, mucus hypersecretion and chronic cough lasting for periods longer than 2 months. However, current therapeutic approaches have been proving to be ineffective in preventing or reversing all the pathological aspects of the disease. Therefore, the development of new therapeutic approaches that are safe and effective are of fundamental importance in the treatment of patients affected by canine chronic bronchitis. Stem cell therapy has been presented to the veterinary market as a safe and effective therapeutic option in the treatment of different diseases that affect small and large animals. Thus, the present study aims to analyze the safety and efficacy of the treatment of canine chronic bronchitis, through stem cell transplantation.